1977
DOI: 10.1111/j.1432-1033.1977.tb11787.x
|View full text |Cite
|
Sign up to set email alerts
|

Further Evidence that Elongation Factor 1 Remains Bound to Ribosomes during Peptide Chain Elongation

Abstract: This paper describes three types of experiments which indicate that the binding sites for elongation factor 1 (EF-1) and elongation factor 2 (EF-2) on ascites cell ribosomes are not identical and perhaps not even overlapping. The experimental evidence presented includes direct competitive binding of labeled elongation factors to ribosomes as well as the influence of pokeweed antiviral protein and Escherichia coli anti-L7/L12 proteins on the binding and function of the two factors. It is further shown that EF-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
9
1

Year Published

1978
1978
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 34 publications
3
9
1
Order By: Relevance
“…Using diphtheria toxin-mediated ADP-ribosylation to assay for EF-2, it was shown that inhibition of EF-2 binding to pre-translocative ribosome Á EF-1a complexes prevented ribosomal translocation. Employing didemnin B as a tool, evidence was provided that EF-1a remains bound to the ribosome throughout the elongation cycle consistent with the model proposed previously by Grasmuk et al 123,124 and supported by other authors. 125 In this model, two mechanisms for inhibition of EF-2 binding may be considered: a competitive mechanism in which didemnin B or EF-1a occupy the ribosome where EF-2 normally binds, or an uncompetitive mechanism in which didemnin B binds to ribosome Á EF-1a complex and locks the complex in a conformation that disfavors EF-2 binding.…”
Section: Didemnin Binding Proteins Ef-1a and Ppt1supporting
confidence: 70%
“…Using diphtheria toxin-mediated ADP-ribosylation to assay for EF-2, it was shown that inhibition of EF-2 binding to pre-translocative ribosome Á EF-1a complexes prevented ribosomal translocation. Employing didemnin B as a tool, evidence was provided that EF-1a remains bound to the ribosome throughout the elongation cycle consistent with the model proposed previously by Grasmuk et al 123,124 and supported by other authors. 125 In this model, two mechanisms for inhibition of EF-2 binding may be considered: a competitive mechanism in which didemnin B or EF-1a occupy the ribosome where EF-2 normally binds, or an uncompetitive mechanism in which didemnin B binds to ribosome Á EF-1a complex and locks the complex in a conformation that disfavors EF-2 binding.…”
Section: Didemnin Binding Proteins Ef-1a and Ppt1supporting
confidence: 70%
“…The N-terminal sequence of P2 is analogous to that of Escherichia coli L7/L12 [35, 361. Furthermore, employing ribosomes and EF-2 from ascites tumor cells, Gasmuck et al [37] reported that antiserum against E. coli L7/L12 proteins inhibited binding of [3H]EF-2 Table 1. Summary ofproteins cross-linked to EF-2 with 2-iminothiolane The relative molecular masses of cross-linked protein dimers of EF-2 -ribosomal-protein were calculated from their migrations in the first dimension on diagonal gel electrophoresis.…”
mentioning
confidence: 99%
“…The N-terminal sequence of P2 is analogous to that of Escherichia coli L7/L12 [35, 361. Furthermore, employing ribosomes and EF-2 from ascites tumor cells, Gasmuck et al [37] reported that antiserum against E. coli L7/L12 proteins inhibited binding of [3H]EF-2 Table 1…”
mentioning
confidence: 99%
“…These initial reports came from studies on the silk worm [4], pig liver [ 5 ] , and more recently on systems derived from the cysts of the brine shrimp, Artemia salina [l]. Intensive efforts in the past to observe such an activity in the Krebs I1 mouse ascites tumor cell system failed although eEF-Ts from Arternia showed stimulating activity in the ascites cell-free protein-synthesizing system [6]. This evidence led us to the conclusion that the activity was not to be found in ascites cells.…”
mentioning
confidence: 99%